A Pragmatic Study of Consolation in the Holy Qur’an - Rasha Ali Alubeidi (مجلة الباحث, 2026)
The Qur’an is central to the psychological, spiritual, and moral lives of all Muslims. One of the major communicative functions of the Qur’an is to provide consolation (a sense of comfort, reassured confidence, and inner peace) to both individuals and communities who are suffering from fear, grief, hardship, and anxiety about their life. This study aims to investigate the concept of "consolation" in the Qur’an from a pragmatic point of view; speech acts, politeness strategies, and illocutionary force. The analysis shows how divine communication has the ability to console the Prophet Muhhamed (PBUH) when he suffered distress and disbelieving. The study employs a qualitative descriptive-analytical methodology which includes insights from pragmatic theories. The results of this study demonstrate that Qur’anic consolation is systematically realized with assertive, directive, expressive, and commissive speech acts, reinforced by divine politeness strategies (reassurance, honorifics, mitigation, and empathy). Finally, the study concludes that while Qur’anic consolation is thematic, it is also basically encoded in the linguistic and pragmatic structure of the Qur’an, making it a powerful and enduring source of human psychology and spirituality.